ANALYSIS OF THE ROLE OF MIDWIVES ON THE SELECTION OF IMPLANTED CONTRACEPTIVE USE BY ACCEPTORS: A LITERATURE REVIEW - Polanda Y Runtoboi; Mardiana Ahmad; Andi Nilawati Usman (Nurse and Health: Jurnal Keperawatan, 2022)
Background: Indonesian family profiles reported the percentage of active acceptors in couples of childbearing ages in 2017 was 63.22%, and the number who never used contraceptives was 18.63%. The highest contraceptive use in Bengkulu province was 71.98%, and the lowest in Papua was 25.73%. The population of Papua Province in 2020 amounted to 4.3 million people or an increase of 1.47 million. Objectives: This study aims to find the role of midwives against the selection of the use of implanted contraceptives by acceptors. Design: This research design is a systematic review to find and review articles from databases and theories that are descriptive. Data Sources: Search articles using databased ScienceDirect and Google Scholar including the keyword "contraceptive implants" with a period of 2018 to 2021; 15 articles are available based on inclusion criteria article discussing implant contraceptives, Year of publication 2018-2021, International and National Publications, the National Journal has ISSN, articles using Indonesian and English Review Methods: Systematic review methods based on established criteria, then collected and made journal summaries include the name of the researcher, the year of publication of the journal, the title of the study, the method, and a summary of the results or findings. by identifying, evaluating and synthesizing the summary of research journals entered into the table according to the format. Results: From the journal filtering, 15 articles were eligible based on the inclusion criteria, it was found that: The role of health workers/midwives is the most important factor in the use of implants contraception by acceptors so that it is hoped that education regarding the benefits of implants can be increased. Conclusion: Interpersonal communication or counseling needs to be improved. Counseling is communication between clients and health workers to facilitate and advocate on any issues related to comprehensive reproductive health. It is expected that with counseling provided by birth control, acceptors can make their own decisions in accordance with the desired method.